Pengaruh Kualitas Layanan terhadap Kepuasan Pelanggan Primajasa Kota Bandung (Studi Pada Rute Bandung-Bandara Internasional Soekarno Hatta Tahun 2023) - Ilmayanti Nur Suriah; Heppy Millanyani (J-MAS (Jurnal Manajemen dan Sains), 2023)
One of the main destinations for domestic and foreign tourists is the city of Bandung which has a lot of charm. The growing development of tourism in Indonesia has also triggered the development of travel service companies, one of which is PT Primajasa Perdanaraya Utama, which is a provider of transportation services in the city of Bandung. However, referring to customer reviews on Instagram and Google, there are several bad assessments regarding the various problems that customers complain about regarding the quality of service that must be improved in order to survive in an increasingly competitive environment. Service quality is a company's various efforts to meet customer expectations, while customer satisfaction is a measure of the ability of the company's products and services to meet customer needs. The purpose of this research is to see the impact of service quality using dimensions (tangible, reliability, responsiveness, assurance and empathy) on primajasa customer satisfaction by using quantitative methods. The results of this study confirm that the four dimensions of service quality (tangible, reliability, assurance, as well as empathy) have a positive and significant impact on customer satisfaction, while the responsiveness dimension has a negative and significant impact on customer satisfaction. Through this study it is known that the empathy dimension has the greatest impact on customer satisfaction, so that primajasa is advised to make several improvements, namely adding free wifi facilities on the bus, improving good interpersonal communication by adding job descriptions to the staff on duty at the entrance to greet each customer arrival and ask for their needs and desires, then the primajasa can also review and maximize departure hours, by providing departures every 1 hour in order to meet customer needs and before departure the primajasa is advised to check again carefully on the tickets and customer luggage to avoid mistakes. The results of this study are expected to become considerations and suggestions that play a role in assisting companies in developing competitive strategies.